2013
DOI: 10.1016/j.jweia.2013.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic stability of road vehicles in dynamic pitching motion

Abstract: The main object of the present study is to investigate numerically the mechanism of aerodynamic damping of pitching oscillation in sedan-type vehicles. The transient numerical solver employed is based on the Large Eddy Simulation (LES) method. Whilst, the Arbitrary Lagrangian-Eulerian (ALE) method was used to realize the vehicle motion during dynamic pitching and fluid flow coupled simulations. Validation of the numerical method was done by comparing the flow structures obtained from the LES to the correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Its cross section covered 5 times the length upstream and 10 times the length downstream of the CAD vehicle model, 4 times the width on both left and right sides, and the height was 5 times the height of the model. The corresponding blockage ratio was about 1.12% according to our measurements, which is within the scope of 5% in typically accepted automobile aerodynamic testing (see [29]). The triangle mesh was set as 10 mm, and the hybrid tetrahedron was 10-200 mm.…”
Section: Figure 12supporting
confidence: 70%
See 1 more Smart Citation
“…Its cross section covered 5 times the length upstream and 10 times the length downstream of the CAD vehicle model, 4 times the width on both left and right sides, and the height was 5 times the height of the model. The corresponding blockage ratio was about 1.12% according to our measurements, which is within the scope of 5% in typically accepted automobile aerodynamic testing (see [29]). The triangle mesh was set as 10 mm, and the hybrid tetrahedron was 10-200 mm.…”
Section: Figure 12supporting
confidence: 70%
“…In the long-term research of Cheng et al [27][28][29], they built various CAD car body models with different complexity to explore the influence of A-pillar and C-pillar of automobiles of different shape (rounded or angular) on driving pitching stability. In their research in 2014 [29], they used the large eddy simulation method on two CAD models with full details; they drew the conclusion that the vortex shed from the A-pillar edge results in a destabilizing tendency while the vortex shed from the C-pillar edge results in a stabilizing tendency. Hassan et al [30] reduced the drag coefficient by nearly 10% by optimizing the angle of departure and the shape of the Rear body diffuser in a racing car CAD model.…”
Section: Introductionmentioning
confidence: 99%
“…Aschwanden et al (2008) used the wind tunnel to study the ride height change of the race cars, and found that the motion aerodynamic caused greater effects on the simplified race car model in the simulated movement. Cheng et al (2013) studied the influence of different combinations of A, C pillar to the aerodynamic stability of the vehicle, and found the importance of the proper shaping of A-pillar and C-pillar to control the vehicle body pitching oscillation. However, their researches mainly focused on transient aerodynamics force to the stability of vehicle, the mechanism of the transient flow field has not been studied yet.…”
Section: Nomenclaturementioning
confidence: 99%
“…These two types of analyses are sometimes combined to solve the FSI problem. Cheng et al (2013) in their research studied car body aerodynamic damping during pitching. To do that, they selected the transient numerical simulation based on the LES method and the vehicle motion was realized with the arbitrary Lagrangian-Eulerian (ALE) method.…”
Section: Introductionmentioning
confidence: 99%